Analisis Kinerja Keuangan PT Mandala Multifinance,Tbk - Gunarso, Amelia Marisa, Dra. Chuzaimah, M.M (2015)
This research purposes to know ability financial performance at PT MANDALA MULTIFINANCE, Tbk for 3 year are 2010-2012. Population of this research is PT Mandala Finance, Tbk and sample of this research is for 3 years in Indonesia Stock Exchange. Base on result of the research gross profit margin at 2010 is 0.843, at 2011 increase 0.878 and at 2012 increases 0.897 and net profit margin at 2010 is 0.155 while net profit margin at 2011 decrease 0.154 and at 2012 increase 0.168. account return on investment above year 2010 get result 4.24, at 2011 increase result is 4.77 and at 2012 result increases 5.37. Account ROE at 2010 is 22.72 while ROE at 2011 increase 24.88 and ROE at 2012 decrease 24.74 ROE measure capital from 2010 to 2012 is fluctuation. It is increasing and decreasing every year. Result cycle account receivable at 2010 is 0.299, at 2011 increases 0.335 and at 2012 increase 0.345. The result means account receivable every year increases. Calculating total asset turnover at 2010 is 0.73 increases at 2011 is 0.309 and at 2012 also increases 0.318. Total asset turnover increases every year. Calculating inventory turnover at 2010 is 33.55 and at 2011 increases 38.27 and at 2012 also increases 40.69. It means inventory turnover ratio increases every year.